THE EFFECT OF CORPORATE GOVERNANCE, COMPANY MEASURE, AND CAPITAL STRUCTURE OF PROFITABILITY AND THE VALUE OF THE FIRM IN TEXTILE AND GARMENT INDUSTRY WAS LISTED IN INDONESIA STOCK EXCHANGE - Perduti Lestari Rulimo; Syamsu Alam; Erlina Pakki (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Raden Fatah Palembang, Indonesia, 2019)
This research aims to find out the effect of corporate governance, company size and capital structure on profitability and firm value in textile and garment industry companies listed on the Indonesia Stock Exchange. Corporate governance variables are measured by independent commissioners. Company size variable is measured by SIZE. Capital structure variables are measured by Debt to Equity Ratio (DER). The profitability variable is measured by Return on Equity (ROE). The population in this research is the textile and garment industry sub-sector manufacturing companies listed on the IDX. The sampling method used was purposive sampling method. Data sources are secondary data collected by documentation techniques. This study uses descriptive statistics and inferential statistics with a quantitative approach and uses panel data regression techniques assisted by the Eviews version 9 program. The results showed that first, the independent commissioner had a positive and not significant effect on Return on Equity. Second, SIZE has a negative and not significant effect on Return on Equity. Third, Debt to Equity Ratio has a positive and significant effect on Return on Equity. Fourth, independent commissioners have a positive and significant effect on tobin’s Q. fifth, SIZE has a positive and significant effect on tobin’s Q. sixth, Debt to Equity Ratio has a negative and significant effect on tobin's Q. seventh, independent commissioners have no effect on tobin’s Q through Return on Equity. eighth, SIZE has no effect on tobin’s Q through Return on Equity. ninth, Debt to Equity Ratio affects tobin's Q through Return on Equity and Tenth, profitability has a positive and significant effect on tobin’s Q